Penerapan Teknik Vokal Artikulasi pada Lagu Indahnya Saat Teduh oleh Pemimpin Pujian di Gereja Methodist Indonesia Sukarame Baru Resort Sukasari Labuhan Batu Utara Tahun Pembelajaran 2023/2024 - Helmalia Diwani Lumban Tobing; Eben Haezarni Telaumbanua; Monang Asi Sianturi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research aims to find out good vocal training techniques for singing for worship leaders by applying articulatory vocal techniques. Articulated vocal technique is the pronunciation of the words in the song lyrics clearly and correctly so that the message and meaning of the song being sung can be heard clearly to the listener. The method used in this research stage is descriptive qualitative method. The stages of research on the application of vocal articulation techniques carried out include observation, interviews and documentation. The objects of this research were five worship leaders at GMI Sukarame Baru Resort Sukasari Labuhan Batu Utara. In the implementation process, researchers held six meetings providing material and singing practice according to correct vocal technique. In this research process, the worship leader practiced articulation repeatedly singing the song "The Beauty of Teduh Time" with examples and practice provided by the researcher during the research, so that in the end the worship leader could understand the material presented by the researcher. The results of this research show that the application of articulatory vocal techniques can improve the singing ability of praise leaders at GMI Sukarame Baru Resort Sukasari Labuhan Batu Utara so that the pronunciation of the words in the song lyrics can be heard clearly when leading praise. Based on this research, the author suggests that GMI Sukarame Resort Sukasari Labuhan Batu Utara Baru continue to develop vocal technique training for worship leaders so that the quality and ability of singing increases.